2009
DOI: 10.1051/forest/2008091
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of organosilicon compounds to reduced leaching of biocides in wood protection

Abstract: Abstract• Leaching of biocide treated wood leads to reduced effectiveness and potential threat to the environment.• Therefore the effectiveness of organosilicons as protective systems of biocides was evaluated. Scots pine sapwood specimens were impregnated with solely organosilicons and biocides as well as with combinations of both.• The biocides 3-iodo-2-propynylbutylcarbamate, propiconazole and 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride confirmed their effectiveness regardless the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The above results suggest addition of biocides to further improve wood durability. On the other hand, De Vetter et al (2009) combination of organosilanes and biocides neither change the protective effectiveness of the treated wood nor reduce the toxicity of their leachates either. However, the authors have tested other alkoxysilanes and only in laboratory conditions.…”
Section: Aboveground Testmentioning
confidence: 95%
“…The above results suggest addition of biocides to further improve wood durability. On the other hand, De Vetter et al (2009) combination of organosilanes and biocides neither change the protective effectiveness of the treated wood nor reduce the toxicity of their leachates either. However, the authors have tested other alkoxysilanes and only in laboratory conditions.…”
Section: Aboveground Testmentioning
confidence: 95%
“…Although similar performances were obtained for the white spruce while using only propiconazole, the use of AOs could also improve the depth of the impregnation of the fungicides and increase their resistance to leaching. De Vetter et al (2009) vacuum treated Scots pine with IPBC (1.5-2 kg/m 3 ) and a mix of IPBC (1.5-2 kg/m 3 ) and propiconazole (2.5-4 kg/m 3 ). They found nearly no mass loss after 16 weeks of exposure to C. puteana, which isn't surprising as this retention is way higher than the suggested retention for these products (EC Directive 98/8/EC 2007; EC Directive 98/8/EC 2008).…”
Section: Amine Oxide Timementioning
confidence: 99%
“…The same combinations of organosilicons and biocides as used in De Vetter et al (2009b) were applied. Briefly, a 5 % solution of the DMS/n-OTES 2 was combined with (1) 0.3 % 3-iodo-2-propynyl-butyl carbamate (IPBC); (2) 0.3 % IPBC in combination with 0.6 % (±)-(cis+trans)-1-(2-(2,4-dichlorophenyl)-4-propyl-1,3-dioxolan-2-yl-methyl)-1H-1,2,4-triazole (propiconazole) and (3) 2 % 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride (Si-Quat).…”
Section: Productsmentioning
confidence: 99%
“…However, most studies found that treatment of wood with organosilicons can only lead to a significant improvement of the investigated property when applied at (very) high concentrations (Hill et al 2004;Weigenand et al 2007;De Vetter et al 2009a). Treatments at lower, economically feasible concentrations lead to only modest improvements of the wood properties (Goethals and Stevens 1994;Mai et al 2005;De Vetter et al 2009b). Nevertheless, most of these authors conclude that wood treatment with an organosilicon may contribute significantly to prolong the service life of the wooden element when applied as part of a more complex (preservative containing) formulation for use class three applications like exterior cladding (Mai et al 2005;Donath et al 2006;De Vetter et al 2009a;b).…”
Section: Introductionmentioning
confidence: 99%